Land Sovereignty as A Counter-Hegemony Against The Corporate Food Regime - Mujib, Taufiqul (BHUMI: Jurnal Agraria dan Pertanahan, 2020)
Abtract: The global food regime has failed and led to a food crisis. However, food regime can transform from time to time in order to dominatethe food system globally. The current food regime is also known as the corporate food regime. In this period, capital accumulation reorganization is no longer centered in the state, but in multinational corporations. Therefore, there needs to be a framework to address the transformation in order to provide an effective alternative food system, especially for the Global South. This study elaborates on how land sovereignty initiated by La Via Campesina can be a counter-hegemony against the corporate food regime to get out of the crisis of capital accumulation through massive land investments, especially in the Global South. Moreover, this paper refers to Friedmann and McMichael’s (1989) concept about the food regime and examines such conditions by using Gramsci’s (1971) ideas on hegemony. In conclusion, the land sovereignty concept can be considered to be an effective alternative framework to deal with the hegemony of neoliberal globalism for five reasons, namely: 1) the possibility of using various property rights systems; 2) the possibility to be implemented through land reform redistribution policy with several adjustments; 3) the probability to be a common platform because the concept recognizes land not only as a resource but also as culture and as a landscape; 4) the probability to be connected with other campaigns; and 5) the probability to be connected with political work of the broader working community globally. Intisari: Rezim Korporasi Pangan telah gagal dan memicu terjadinya krisis pangan. Meskipun demikian, rezim pangan dapat bertransformasi dari waktu ke waktu untuk menghegemoni sistem pangan secara global. Rezim pangan saat ini juga juga dikenal sebagai rezim korporasi pangan. Dalam periode ini, reorganisasi akumulasi kapital tidak lagi berpusat pada negara, tetapi pada korporasi-korporasi multinasional. Oleh karena itu perlu adanya sebuah kerangka untuk menjawab transformasi tersebut sehingga mampu menawarkan sebuah sistem pangan alternatif yang efektif, khususnya bagi negara-negara Global Selatan. Kajian ini mengelaborasi bagaimana kedaulatan tanah yang diinisiasi oleh La Via Campesina dapat menjadi kontra hegemoni melawan rezim korporasi pangan untuk bisa keluar dari krisis akumulasi kapital akibat investasi-investasi tanah yang masif terutama di Global Selatan. Tulisan ini merujuk pada konsep dari Friedmann dan McMichaels (1989) mengenai rezim pangan dan mengkaji beberapa situasi dengan menggunakan ide Gramsci mengenai hegemoni. Kesimpulannya, konsep kedaulatan tanah dapat dipertimbangkan sebagai sebuah alternatif kerangka yang efektif untuk menghadapi hegemoni globalisme neoliberal untuk 5 alasan, yaitu: dimungkinkannya menggunakan berbagai sistem hak kepemilikan, kemungkinan untuk diimplementasikan melalui kebijakan land reform redistributif dengan sejumlah penyesuaian, peluang untuk menjadi platform umum karena konsep tanah tidak lagi hanya dipahami sebagai sumberdaya, tetapi sebagai budaya dan lanskap, peluang untuk menghubungkannya dengan kampanye yang lain serta kerja politik pada tataran kerja komunitas luas secara global.